History of Uzbek Musicology and Modern Trends in It - Zuparova Fotima Rixsievna (International Journal on Integrated Education, 2022)
All forms of spiritual culture, including song and music, are the product of the practical activities of the broad masses of the people. Music as a science has been deeply studied by our ancestors since time immemorial and wonderful works has come down to us. MUSIC (Greek mousiche - the art of muses) - a type of art that reflects the range of human emotional experiences, thoughts, imagination through a sequence or set of musical sounds (tones, melodies). Its content consists of certain musical artistic images that represent changing moods. Music incorporates different human moods (e.g., elation, joy, pleasure, observation, sadness, fear, etc.). In addition, music vividly reflects the volitional qualities of a person (determination, aspiration, thoughtfulness, composure, etc.), as well as his nature (client).